1995
DOI: 10.1007/bf01991916
|View full text |Cite
|
Sign up to set email alerts
|

The Antley-Bixler syndrome: Report of two familial cases with severe renal and anal anomalies

Abstract: Renal agenesis and imperforate anus may occur in the Antley-Bixler syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…4,5,12 Other prenatal sonographic features such as hypertelorism, palpebral edema, exophthalmia, polyhydramnios, choanal atresia (demonstrated by lack of communication between the nostrils and nasopharynx by Doppler evaluation), lemon-shaped skull, horseshoe kidneys, renal agenesis, bowing of the ulna, and absence of nasal bones have also been reported. [4][5][6]12,32 In addition to the clinical and sonographic features, ABS/PORD has been associated with extremely low (or undetectable) maternal serum estriol levels, as was evident in this case. Consequently, maternal serum estriol levels may strengthen the prenatal diagnosis of ABS.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…4,5,12 Other prenatal sonographic features such as hypertelorism, palpebral edema, exophthalmia, polyhydramnios, choanal atresia (demonstrated by lack of communication between the nostrils and nasopharynx by Doppler evaluation), lemon-shaped skull, horseshoe kidneys, renal agenesis, bowing of the ulna, and absence of nasal bones have also been reported. [4][5][6]12,32 In addition to the clinical and sonographic features, ABS/PORD has been associated with extremely low (or undetectable) maternal serum estriol levels, as was evident in this case. Consequently, maternal serum estriol levels may strengthen the prenatal diagnosis of ABS.…”
Section: Discussionsupporting
confidence: 57%
“…2,[5][6][7]20,[27][28][29]31 Other malformations such cardiac defects, renal duplication, large clitoris, imperforate anus, cryptorchidism, fused labia majora, and hydrocephalus have been desc ribed. 2,6,20,32,33 ABS has classically been identified at newborn or childhood examination using radiography, computed tomography, magnetic resonance imaging, or stillbirth autopsy. However, in recent years, ultrasonography has enhanced the prenatal diagnosis of ABS as it is able to document many of the clinical features associated with this syndrome prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that while cases of ABS with FGFR2 mutations had normal genitalia [34, 36, 40, 41], reported cases of ABS with apparent autosomal recessive inheritance had genital abnormalities [19, 38, 39, 43]. FGFR2 mutations were found in 7 of 16 ABS patients, but FGFR2 mutations and genital abnormalities segregated completely [19].…”
Section: Antley-bixler Syndromementioning
confidence: 99%
“…The genetics of ABS was initially controversial: reports of affected siblings [37, 38] and parental consanguinity [39] suggested autosomal recessive inheritance, but autosomal dominant fibroblast growth factor receptor 2 (FGFR2) mutations have been found in a number of cases [19, 34, 36, 40, 41]. Fibroblast growth factors (FGFs) are mitogens involved in bone growth and development [42].…”
Section: Antley-bixler Syndromementioning
confidence: 99%
“…[1] Lehuep et al . (1995) reported two affected sibs,[7] in the first case, renal agenesis was recognized prenatally when oligohydramnios led to the sonographic diagnosis of absent kidneys during the seventh month. Clinical features were recognized by ultrasonography at 21 weeks in the second case.…”
Section: Discussionmentioning
confidence: 99%